Pluripotent stem cell-derived chimeric antigen receptor-natural killer cells targeting epidermal growth factor receptor 2 for cancer immunotherapy - Han, Jongsuk; Jin, Chaeyeon; Hwang, Sae-Byeok; Lee, In Jee; Baek, Young Seok; Jung, Daun; Kim, Ki Yeon; Mitalipov, Shoukhrat; Kim, Ji Hyang; An, Hee Jung; Lee, Yeonmi; Kang, Eunju (BMB reports, 2025)
Chimeric antigen receptor-natural killer (CAR-NK) cells are emerging as a promising platform for allogeneic, cell-based immunotherapy. Among available sources, NK cells derived from pluripotent stem cells (PSCs) provide a renewable and scalable option that overcomes the limitations of primary NK cells. Human epidermal growth factor receptor 2 (HER2), a membrane protein frequently overexpressed in many solid tumors, is an attractive target for cancer immunotherapy. In this study, we designed a green fluorescent protein (GFP)-linked anti-HER2 CAR construct and introduced it into PSCs via lentiviral transduction. Three stable PSC-derived clones (CAR-A, CAR-B, and CAR-C) were established, each co-expressing anti-HER2 CAR with GFP. After differentiation under xeno-free and feeder-free culture conditions, CAR expression was maintained in NK cells. The resulting PSC-derived CAR-NK cells displayed phenotypic and functional features comparable to wild-type PSC-derived NK cells, while showing markedly enhanced cytotoxicity against HER2-positive cancer cell lines. These findings demonstrated the potential of the use of PSC-derived anti-HER2 CAR-NK cells as a robust and scalable immunotherapy. In addition, this platform could be extended to produce CAR-NK cells directed against a wide range of tumorassociated antigens. [BMB Reports 2025; 58(11): 475-483].